Association between Resilience, Stress, and Mental Well-being of Nursing Students - Florensa, Maria Veronika Ayu; Juniarta, Juniarta; Purimahua, Dora Irene (Universitas Aisyah Pringsewu, 2022)
Nursing students who are prepared to be professional nurses need to have holistic health. Health is not only physical but also mental. The educational process taken; both theories in the classroom and practical learning experiences can cause stress to students. Resilience is the ability to bounce back after facing a problem, which is needed so students can carry out their education process well. This study aimed to identify the relationship between resilience and stress and the mental well-being of nursing students. This research is quantitative correlational research with a cross-sectional design. The study population was nursing students in Jakarta, Bogor, Depok, Tangerang, and Bekasi, and with the purposive sampling technique, a sample of 223 students was obtained. The instruments used in this study were valid and reliable, including The Resilience 14 questionnaire (alfa Cronbach 0.76), the Stress in Nursing Education Questionnaire (Cronbach 0.946), and The Warwick-Edinburgh Mental Well-being Scales (Cronbach 0.84). The result of the study was that 64.1% of students had high resilience, 62.8% experienced severe stress, and 75.3% had an average mental well-being level. There is a relationship between resilience and stress and the mental well-being of students (p less than 0.05). Severe stress conditions experienced by nursing students do not necessarily decrease their resilience and mental well-being. Stress management interventions are needed so nursing students can complete their education, maintain high and improve mental well-being. Abstrak: Mahasiswa keperawatan yang dipersiapkan menjadi perawat professional membutuhkan kesehatan yang holistic. Kesehatan tidak hanya meliputi aspek fisik namun juga jiwa atau psikologis. Proses pendidikan yang dilalui mahasiswa keperawatan baik perkuliahan di kelas maupun pembelajaran praktik dapat menyebabkan stres pada mahasiswa. Resiliensi adalah kemampuan untuk dapat bangkit Kembali setelah menghadapi masalah dibutuhkan oleh mahasiswa sehingga mereka dapat melalui pendidikannya dengan baik dengan kondisi kesejahteraan jiwa yang baik pula. Tujuan penelitian ini yaitu untuk mengetahui hubungan antara resiliensi dengan stress dan resiliensi dengan kesejahteraan jiwa mahasiswa keperawatan. Penelitian ini merupakan penelitian kuantitaif korelasional dengan desain cross sectional. Populasi penelitian ini adalah mahasiswa keperawatan yang berlokasi di Jakarta Depok, Bogor, Tangerang dan Bekasi dan dengan teknik convenience sampling didapatkan sejumlah 223 responden. Instrumen yang digunakan dalam penelitian ini antara lain The Resilience 14 questionnaire (Cronbach 0.76), the Stress in Nursing Education Questionnaire (Cronbach 0.946) dan The Warwick-Edinburgh Mental Well-being Scales (Cronbach 0.84). Hasdil penelitian yaitu 64.1% mahasiswa memiliki reiliensi yang tinggi, 62.8% mengalami stress berat, dan 75.3% memiliki kesejahtaeraan jiwa dalam level rata-rata. Analisis data menggunakan uji gamma menunjukkan ada hubungan yang signifikan antara resiliensi dengan stress dan resiliensi dengan kesejahteraan jiwa (p kurang dari 0.05). Kondisi stress berat yang dialami oleh mahasiswa keperawatan tidak selalu menurunkan resiliensi dan kesejahteraan jiwanya. Interbvensi manajemen stress dibutuhkan sehingga mahasiswa dapat menjalani pendidikannya dengan tetap memelihara resiliensinya tetap baik dan meningkatkan kesejahteraan jiwanya.